Impact of diagnostic bronchoscopy in burned adults with suspected inhalation injury. Issue 6 (September 2019) - Ziegler, Benjamin; Hundeshagen, Gabriel; Uhlmann, Lorenz; Will Marks, Patrick; Horter, Johannes; Kneser, Ulrich; Hirche, Christoph
Highlights: 3014 patients with inhalation injury in the National Burn Repository were analyzed. Patients with undergoing bronchoscopy at admission show a higher risk for pneumonia. Increased mortality is seen when bronchoscopy is performed. Abstract: Introduction: Inhalation injury is a common complication of thermal trauma. Fiberoptic bronchoscopy (FOB) is regarded as current standard practice in diagnosing and grading inhalation injury. Nonetheless, its predictive value in terms of therapeutic decision-making and clinical outcome is controversial. Methods: Adult burn patients with inhalation injury (InI) were selected from the National Burn Repository of the American Burn Association. Subjects were propensity score pair-matched based on injury severity and grouped based on whether or not FOB had been performed (FOB, CTR, respectively). Mortality, incidence of pneumonia, length of hospitalization, length of ICU stay and dependency on mechanical ventilation were compared between the two groups. Results: 3014 patients were matched in two groups with a mean TBSA of 22.4%. There was no significant difference in carboxyhemoglobin fraction at admission. Patients, who underwent FOB on admission had a significantly increased incidence of pneumonia (p < 0.001), mortality (p < 0.05), length of hospitalization (p = 0.002), ICU stay (p < 0.001) and duration of mechanical ventilation (p = 0.006). In a subgroup analysis of patients with TBSA of at least 20%, incidence of pneumonia was significantly higher in the FOB group (p < 0.001) and longer mechanical ventilation was required (p = 0.036). Discussion: Diagnosis and grading of InI through FOB is the current standard, although its predictive value regarding key outcome parameters and therapeutic decision-making, remains unclear. The potential procedural risk of FOB itself should be considered. This study demonstrates correlations of FOB with major clinical outcomes in both a general collective of burned adults as well as severely burned adults. Although these findings must be interpreted with caution, they may induce further research into potential harm of FOB and critical review of routine diagnostic FOB in suspected inhalation injury in thermally injured patients.